Soil bacterial community structure remains stable over a 5-year chronosequence of insect-induced tree mortality - Ferrenberg, Scott; Knelman, Joseph E.; Jones, Jennifer M.; Beals, Stower C.; Bowman, William D.; Nemergut, Diana R. (Frontiers in Microbiology, 2014)
Extensive tree mortality from insect epidemics has raised concern over possible effects on soil biogeochemical processes. Yet despite the importance of microbes in biogeochemical processes, how soil bacterial communities respond to insect-induced tree mortality is largely unknown. We examined soil bacterial community structure (via 16S rRNA pyrosequencing) and community assembly processes (via null deviation analysis) along a five-year chronosequence (substituting space for time) of bark beetle-induced tree mortality in the southern Rocky Mountains, USA. We also measured soil microbial biomass and soil chemistry, and used in situ experiments to assess inorganic nitrogen mineralization rates. We found that bacterial community structure and assembly―which was strongly influenced by stochastic processes―were largely unaffected by tree mortality despite increased soil ammonium (NH4+) pools and reductions in soil nitrate (NO3-) pools and net nitrogen mineralization rates after tree mortality. Linear models suggested that microbial biomass and bacterial phylogenetic diversity are significantly correlated with nitrogen mineralization rates of this forested ecosystem. However, given the overall resistance of the bacterial community to disturbance from tree mortality, soil nitrogen processes likely remained relatively stable following tree mortality when considered at larger spatial and longer temporal scales—a supposition supported by the majority of available studies regarding biogeochemical effects of bark beetle infestations in this region. Our results suggest that soil bacterial community resistance to disturbance helps to explain the relatively weak effects of insect-induced tree mortality on soil N and C pools reported across the Rocky Mountains, USA.